Improving Student's Vocabulary Skill Through Contextual Teaching and Learning (CTL) Method At The Nineth Years Student's of Pondok Pesantren Salafiyah Wustho An Nimah Batam - Regandi, Angga; Edi , Warno; Adam , (International Journal of Scientific Research and Management (IJSRM), 2024)
This thesis discusses about Improving students' vocabulary skills through contextual learning (CTL) in ninth grade students of Pondok Pesantren Salafiyah Wustho An Nimah Islamic. The formulation of the problem in this study is "The effectiveness and perception of students in the use of contextual learning (CTL) to improve students' vocabulary. The goal of this study is to determine whether the use of contextual learning (CTL) can improve students' vocabulary skill and also students' perceptions in teaching vocabulary through CTL. This study uses a pre-experimental method with post-test. This study aims to reveal or describe systematically based on data that has been collected from the pre-experimental study. The target population of this study were all ninth grade students of Salafiyah Wustho An Nimah Pondok Pesantren in 2023/2024 year. The sample was taken from the population using purposive sampling and from the lower class and the number of sample were 23 students. The instruments of this study were vocabulary tests and questionnaires. The vocabulary test was given to which students understood the material given and the questionnaire was to determine students' perceptions. The results of the analysis show a significant difference between before and after giving treatment through the CTL method in improving vocabulary skills. Based on the results of the analysis, it can be concluded that the CTL method is effective in improving the vocabulary skills of class IX students of the Pondok Pesantren Salafiyah Wustho An Nimah.